Can metal cations electrocatalyze sulfur redox reaction and suppress polysulfide shuttle? - Kumar, Subramani; Swain, Gitanjali; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2023)
In lithium-sulfur (Li-S) batteries, sulfur undergoes various changes. It switches between cyclic structure and linear structure. The charge on the sulfur varies between a neutral state and a negative charge-bearing state. Due to these changes, the sulfur/polysulfide dissolves in the battery electrolyte. Furthermore, the kinetics of the sulfur redox reaction is sluggish. Therefore, a material that can suppress sulfur/polysulfide dissolution and electrocatalyze sulfur redox reaction is needed. We hypothesize that the polysulfide dissolution can be suppressed if the host exhibits polyvalent electrostatic attraction. Polysulfide is a negative charge-bearing molecule; hence the host must comprise multiple positive charges. Nickel cations with other heteroatoms have been explored as a host in Li-S batteries. The heteroatoms impart additional interactions. The easier way to circumvent the effect of heteroatoms is the addition of metal salts. However, metal salts can either exhibit monovalent or divalent attraction with polysulfides. Those interactions are weak and we must have polyvalent interaction. Towards this objective, we have designed and synthesized a material that comprises multiple divalent cations that is also devoid of heteroatoms. The Li-S batteries fabricated using the metal cation immobilized graphene showed a maximum specific capacity of 1022 mAh/g at 0.1 C rate. Among the metal cations, nickel cations showed better performance than cobalt cations. Thus, we demonstrate that metal cations immobilized on Graphene can efficiently electrocatalyze the sluggish sulfur redox reaction and suppress the polysulfide dissolution.
Keywords: electrocatalysis; graphene; lithium-sulfur batteries; metal cations; polysulfides

i-Indigo-based self-assembled microparticles and their conversion to nanoparticles - Singh, Anup Kumar; Swain, Gitanjali (ChemistrySelect, 2023)
Microscopic particles (MPs) are used to scatter and reflect UV light. It is well established that inorganic MPs such as TiO2 and ZnO produce carcinogens. Therefore, organic MPs are explored for UV absorption. Conjugated chromophores with differing lipophilicity usually self-assemble into nanoscopic structures. In our previous experiments, unsymmetrical i-Indigo was found to self-assemble into 500 nm particles. We hypothesized that the size of the self-assembled particles can be increased by increasing the lipophilicity difference between the side chains. Toward this objective, we have chosen the i-Indigo core with TEG and alkyl chains as side chains. As a result, the i-Indigo molecules were found to self-assemble into 3 & mu; spheres in solution. By substituting side chains with different lipophilicity, i-Indigo microparticles with the size of 5 & mu; are prepared. A careful analysis showed that the spheres are similar to a soccer ball, and they deflate upon drying on the substrate surface. The judiciously chosen side chain binds with a metal-ion (Cs+) and forms nanoscopic assemblies. After Cs+ binding, the size of the particles is decreased drastically to 100 nm. The simple addition of ions converts microscopic assemblies into nanoscopic assemblies.
Keywords: Isoindigo; microparticles; Nanoparticles; Self-assembly; UV absorber

Organic field effect transistors comprising copolymers synthesized without structure-directing moieties with enhanced carrier mobility - Swain, Gitanjali; Javaregowda, Bharathkumar H.; Dambhare, Neha V.; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2023)
Conjugated materials are synthesized by C-C bond formation reactions. Trimethyltin and boronic acid are two widely used structure-directing moieties. While using the ethynyl moiety as a part of the monomer, additional structure-directing moieties are not needed. However, ethynylene will be part of the conjugated material. Often, the polymers with an ethynylene moiety negatively impact the polymers' properties. However, the ethynylene moiety could minimize the dihedral angle if the monomer has steric functionalities. For example, BODIPY is an attractive monomer due to its high molar extinction coefficient, partial quinoidal character, and high quantum yield. However, materials based on BODIPY exhibited poor charge carrier mobility due to steric hindrance generated by four methyl groups. Herein, we copolymerize BODIPY with ethynylene comprising i-indigo and thieno-i-indigo. The copolymer with thieno-i-indigo showed increased molecular weight and significantly reduced band gap compared to the copolymer with i-indigo. The copolymer with i-indigo showed immeasurably low hole transport mobility. On the other hand, the copolymer with thieno-i-indigo exhibited 0.003 cm2V(-1) s(-1). These measurements were made using field effect transistors. We also measured the charge carrier mobility using the space charge-limited current method. Both copolymers exhibited a mobility of 10(-3) cm(2) V-1 s(-1).
Keywords: acetylene linkage; BODIPY; field effect transistor; iso-indigo; Sonogashira coupling; thienoisoindigo

Solvatochromism and side chain effects on the morphological behavior of bodipy-alt-i-Indigo copolymers - Singh, Anup Kumar; Swain, Gitanjali; Birajdar, Sarika (New Journal of Chemistry, 2024)
Among the factors that govern the self-assembly of a molecular system, side chains and solvent polarity play crucial roles in the morphological alteration of small molecules in solutions. Although the effect of side chains on the self-assembly of small molecules has been studied well, reports on their importance in the aggregation behavior of polymers are limited. Investigating whether a minor change in the side chain produce any significant impact on the morphology of the polymer in solution is of great research interest. Towards the end goal, to alter the morphology of polymers and to know the impact of the side chains on the self-assembly properties of the conjugated polymers, two BODIPY-i-Indigo alternating copolymers, P1 [poly(BDP12-alt-iI)] and P2 [poly(BDPE-alt-iI)], were synthesized, and their aggregation behavior was explored in various solvents. Both the copolymers, P1 and P2, exhibited narrow PDI values of 1.16 and 1.45, respectively. Although their cores are the same, P1 showed a thin film morphology, while P2 displayed a porous morphology (approximately 557 nm) in chloroform. On changing the solvent, P1 showed a porous morphology in a 50% THF-CHCl3 mixture. However, in P2, the pores were reduced to extremely small sizes in the 50% THF-CHCl3 mixture. This work demonstrates that even a minimal change in the side chains of copolymers and polarity differences between solvents can produce a drastic morphological effect.

Variations in packing as a function of side chains in random copolymers and its impact on charge carrier mobility - Swain, Gitanjali; Kumar, Subramani; Samudre, Nikhil S. (Macromolecular Chemistry and Physics, 2024)
Homopolymers and alternating copolymers of conjugated molecules exhibit impressive performance in electronic devices. Despite the well-established procedures, the synthesis of alternating copolymers using three monomers is not as easy as random copolymers. Besides facile synthesis, the random copolymers can match the performance of alternating copolymers in electronic devices. Herein, random copolymers are designed and synthesized comprising thienoisoindigo (TIIG), diketopyrrolopyrrole (DPP), and thiophene. The DPP monomers installed with various side chains including branched alkyl chain, branched alkyl chain with ester functionality, linear oligo ethylene glycol, and siloxane terminated alkyl chain are incorporated into the polymers (P1, P2, P3, and P4, respectively). All the thermally stable, low bandgap random copolymers exhibited strong H-type aggregation in thin film. The relationship between thin film microstructure originating from diverse side chains and the charge transport in organic field effect transistors (OFETs) is investigated. All the random copolymers exhibited predominantly p-type charge transport and a maximum hole mobility of 2 x 10-2 cm2 V-1s-1 is observed for P3. The packing of all the polymers is examined theoretically by density functional theory (DFT) and compared with experimental values obtained from grazing incident X-ray diffraction (GIXRD). Various side chains (hydrophilic and hydrophobic) affect molecular packing of random polymers which ultimately affects its thin film morphology and semiconducting performances. Linear chains provide better interchain packing by pi-pi stacking compared to bulky branched side chains. The incorporation of heteroatoms and polar groups into the side chain further enhances the interchain interactions. image
Keywords: diketopyrrolopyrrole; organic field effect transistor; random polymer; side chain engineering; thienoisoindigo

Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR